DSM-5 suicidal behavior disorder: a systematic review of research on clinical utility, diagnostic boundaries, measures, pathophysiology and interventions - Oliogu, Etinosa; Ruocco, Anthony C. (Frontiers in Psychiatry, 2024)
Background It has been a decade since Suicidal Behavior Disorder (SBD) was introduced in Section III of the DSM-5 under “Conditions for Further Study”. SBD is chiefly characterized by a self-initiated sequence of behaviors believed at the time of initiation to cause one’s own death and occurring in the last 24 months. Aims To systematically review empirical studies on SBD to identify primary research themes and promising future research directions. Method A search of empirical articles on SBD published between May 2013 and March 2023 was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Results Screening of 73 records by two independent raters yielded 14 eligible articles. The primary research themes identified from these articles included clinical utility of SBD to predict future suicide risk, association of SBD with closely related disorders, psychometric properties of SBD measures, pathophysiology of SBD, and the effectiveness of interventions for people with SBD. Conclusion Understanding of SBD has slowly progressed since its introduction a decade ago and has mainly been applied in research to define study groups displaying suicidal behavior. The clinical utility of SBD for predicting future suicide risk is low and more research is needed to understand measurement of the diagnosis and its distinctiveness from related disorders and other self-harming behaviors.